A Quality Function Deployment model: Application design for sauce bottle washer - Rahmawati, Berty Dwi; Bayogi Putra Pradana , Igh; Rachman , Buna Rizal (OPSI, 2025)
Small and Medium Enterprises (SMEs) play a crucial role in employment generation and contribute substantially to national economic development, particularly in developing countries. This study examines an SME in Yogyakarta that produces, on average, 175 crates (4,200 bottles) of sauce and 5 crates (1,200 bottles) of sweet sauce daily. The bottle washing process is currently performed manually, requiring up to 3,737 minutes per day. This inefficiency increases labor dependency and delays production due to the unavailability of clean bottles. To address this issue, the study adopts the Quality Function Deployment (QFD) method to translate customer needs into technical specifications for product development. The House of Quality (HoQ) framework is utilized to identify twelve critical product attributes that inform the design of a sauce bottle washer. The resulting design comprises 17 components, including a main frame, dynamo, washing basin, bottle holder, bearing units, inner brush shafts, pulley shafts, brushes, pulleys (2.5-inch and 10-inch), gears, V-belts, chains, caps, wheels, switches, and stoppers. The implementation of this washing system successfully reduces the total bottle washing time by 720 minutes per day. This improvement enables the SME to meet its daily production targets more effectively and contributes to increased operational efficiency.